2002
DOI: 10.1139/z02-161
|View full text |Cite
|
Sign up to set email alerts
|

Gap crossing by chipmunks: an experimental test of landscape connectivity

Abstract: Eastern chipmunks (Tamias striatus) are forest specialists common to eastern North America. Numerous studies suggest that chipmunks require fencerow corridors between woodlots to maintain functional connectivity in agricultural landscapes. We tested this hypothesis by conducting a homing experiment to assess whether chipmunks would cross nonforested gaps of different sizes. Chipmunks in 11 landscapes were translocated a constant distance of 220-250 m across gaps ranging in size from 0 (continuous forest) to 24… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
27
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 39 publications
5
27
0
Order By: Relevance
“…Uezu et al (2005) similarly found that a forest patch that was structurally isolated was functionally connected for three (of seven) Atlantic Forest bird species. Bowman and Fahrig (2002) likewise found woodlots without corridors in Ontario, Canada, functionally connected for chipmunks; biologists previously thought chipmunks were forest specialists who require corridors. THE MATRIX AS SELECTIVE FILTER.-The matrix has been referred to as a selective filter (Gascon et al 1999) in that some species are able to move through the matrix while others are not (Estrada & Coates-Estrada 1996).…”
Section: Discussionmentioning
confidence: 97%
“…Uezu et al (2005) similarly found that a forest patch that was structurally isolated was functionally connected for three (of seven) Atlantic Forest bird species. Bowman and Fahrig (2002) likewise found woodlots without corridors in Ontario, Canada, functionally connected for chipmunks; biologists previously thought chipmunks were forest specialists who require corridors. THE MATRIX AS SELECTIVE FILTER.-The matrix has been referred to as a selective filter (Gascon et al 1999) in that some species are able to move through the matrix while others are not (Estrada & Coates-Estrada 1996).…”
Section: Discussionmentioning
confidence: 97%
“…The moisture content of soils is also often measured using time-domain transmissometry (TDT) [16]. More broadly interpreted connectivity checking also occurs in contexts such as wireless sensor networks [17], power distribution networks [18], graph theory [19], linguistics [20], zoology [21] and medicine [22].…”
Section: Connectivity Checks In the New Blm System 31 Connectivity Cmentioning
confidence: 99%
“…Therefore, we predicted that in addition to habitat area effects, flying squirrel patch occupancy would be positively related to structural connectivity of the forest surrounding the focal habitat patch. Conversely, cursorial squirrels should show a greater tolerance for landscapes with low structural forest connectivity since they do not rely on gliding between trees for movement (e.g., Bowman and Fahrig 2002;Patterson and Malcolm 2010).…”
Section: Introductionmentioning
confidence: 99%